2011
DOI: 10.2298/pan1103343g
|View full text |Cite
|
Sign up to set email alerts
|

An empirical investigation on the determinants of the saving-investment interaction

Abstract: This study aims to shed light on the Feldstein-Horioka (F-H) puzzle, making use of the potential explanations put forward in the related literature. To this end, the study takes a distinct empirical route, combining a cointegration technique and regression analysis. In the first step, we obtain three definitions for the dependent variable that represent the degree of the interaction between domestic saving and investment (S-I), employing a cointegration analysis for 86 countries in the sample. In the sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Kalyoncu (2007) discovered that Denmark, France, Greece, Italy, Japan, Spain, Sweden, Turkey, and the United Kingdom show low capital mobility in OECD countries. Gur, Erden, and Ozkan (2011) found that openness of the economy has no influence on the saving-investment link and found that it is not plausible to use the relationship as an indicator of international capital mobility. Brunel and Sassari (2013) showed that the estimated saving-retention coefficient is close to zero for 21 OECD countries when global shocks are taken into account by common factors.…”
Section: Related Existing Studiesmentioning
confidence: 99%
“…Kalyoncu (2007) discovered that Denmark, France, Greece, Italy, Japan, Spain, Sweden, Turkey, and the United Kingdom show low capital mobility in OECD countries. Gur, Erden, and Ozkan (2011) found that openness of the economy has no influence on the saving-investment link and found that it is not plausible to use the relationship as an indicator of international capital mobility. Brunel and Sassari (2013) showed that the estimated saving-retention coefficient is close to zero for 21 OECD countries when global shocks are taken into account by common factors.…”
Section: Related Existing Studiesmentioning
confidence: 99%